Professional Ethics of Auditors and Its Impact on Audit Quality - Surya, Farhan; Pramudita, Adela; Wijaya, Dini; Permadi, Dodo; Putra, Eka (Manunggal Halim Jaya, 2021)
This study investigates the professional ethics of auditors and its impact on audit quality. A qualitative literature review methodology was employed to synthesize findings from existing studies. The analysis revealed a nuanced relationship between auditors' ethical conduct and audit quality, with some studies indicating a positive association, while others presenting conflicting or inconclusive results. Factors such as organizational culture, ethical training, regulatory mechanisms, and client characteristics were identified as influential determinants of auditors' ethical behavior and audit quality outcomes. Theoretical implications suggest the need for further development to comprehensively understand the determinants and consequences of auditor ethics. Managerial implications highlight the importance of fostering a positive ethical culture, investing in ethical training programs, strengthening regulatory oversight, and prioritizing clients with strong ethical commitments. This study contributes to the ongoing discourse on enhancing the effectiveness of auditing practices and regulatory mechanisms in safeguarding investor interests and maintaining confidence in financial markets.